PENYELESAIAN SENGKETA PEMILIHAN UMUM PRESIDEN TAHUN 2019 MENURUT UNDANG-UNDANG NOMOR 7 TAHUN 2017 TENTANG PEMILIHAN UMUM: Resolution of Disputes Regarding the 2019 Presidential General Election According to Act 7 of 2017 concerning General Elections - Putri Nurmalia Oktaviani; Ferry Edwar (Reformasi Hukum Trisakti, 2024)
The constitution serves as the fundamental basis for a nation, encompassing its system of government and the fundamental rules governing its existence. Despite Indonesia having the 1945 Constitution as its governing document, the electoral process often gives rise to issues, such as disputes over vote counts that are subsequently brought before the Constitutional Court. The formulation of the problem in this article is how the suitability of the Settlement of Presidential General Election Disputes in 2019 with act Number 7 of 2017 concerning General Elections and what are the obstacles to the Settlement of Presidential Election Disputes in 2019. Utilizing literature reviews and secondary data. The research findings affirm that the resolution of disputes related to the 2019 Presidential Election should have been conducted by the institution vested with authority as per the applicable regulations. These disputes arose due to the simultaneous conduct of the General Elections, emphasizing the necessity for proper handling by institutions in accordance with the governing laws. Highlighting the importance of adhering to established procedures and regulations becomes pivotal to ensure the proper resolution of election disputes within the framework of the law.